Sustaining Community Fish Refuges in Cambodia through Community-Based Governance - Baldivieso, Carla; De Silva, Sanjiv; Gleich, Pia; Soeun, Kimourn; Neth, Sreypov; Ou, Phichong; Sun, Vathanak; Sean, Vichet; Oem, Sothanh; Koy, Chandy; Ostrower, Lara; Freed, Sarah; et al. (WorldFish, 2025)
In Cambodia, inland fisheries, including Rice Field Fisheries (RFFs), are a key element of rural food and nutrition security, seasonal income, and an important cultural asset. However, these fisheries are increasingly threatened by habitat loss, changes in land use, overfishing, pollution, and climate change. In response to these pressures, international organizations, government agencies, local NGOs, and local communities have partnered to implement Community Fish Refuges (CFRs) within RFFs to protect fish stocks, increase productivity, and strengthen local food systems. Managed by local communities with support from the Fisheries Administration Cantonment (FiAC) and external parties in the early stages of implementation, CFRs provide multiple benefits including stable aquatic habitats; increased production of aquatic foods; enhanced food and nutrition security; greater supplementary income; groundwater recharge, and climate resilience. However, the sustainability and success of CFRs largely depend on the capacity of local villagers to collaborate and engage in collective action. In this policy brief, some of the challenges of collective management and grassroots decision-making in a rural Cambodia context were examined, and underscored the social dimensions that development actors, policymakers, and funding agencies who initiate development interventions must consider.